Perfil clínico e epidemiológico de pacientes em tratamento antirretroviral atendidos na unidade dispensadora de medicamentos do Hospital Universitário Cassiano Antônio de Moraes - UDM/HUCAM antes e depois da introdução do Dolutegravir - Silva, Givago Gomes da (2020)
Introduction: The description of acquired immunodeficiency syndrome (AIDS) occurred in the early 1980s by the Center for Disease Control and Prevention in the United States of America. The classic characteristic of the infection is the depletion of CD4 + T lymphocytes, with the consequent manifestation of AIDS-defining diseases, such as extrapulmonary tuberculosis and toxoplasmosis. Objective: To evaluate the clinical and epidemiological profile of patients undergoing antiretroviral therapy at the medication dispensing unit of Hospital Universitário Cassiano Antônio de Moraes - UDM / HUCAM before and after the institution of dolutegravir (DTG) as the first line of treatment. Methods: Retrospective cohort study based on secondary data obtained from Logistic Control System for Therapeutic Drugs (SICLOM) OPERACIONAL and Control System for Laboratory Tests of the National Network of Lymphocytes CD4+/CD8+ Count and HIV Viral Load (SISCEL) of patients beginning antiretroviral therapy treated at the UDM / HUCAM. The study included patients aged 18 years or older and who were being followed up on an outpatient basis at HUCAM. The variables studied were: age, gender, marital status, education, CD4 count and viral load. The statistical program used was SPSS version 20 (IBM). In the step of bivariate analysis, tests applied for comparison of categorical variables were Chi-square and Fisher Exact. The comparison of continuous variables involved tests for comparison of means or non-parametric tests. The step of multivariate analysis verified the association between the intervening variables and two different outcomes, namely viral load and discordant immunological response, using binomial logistic regression. The measure of association was represented by the odds ratio (OR) and its respective 95% confidence interval. In the binary logistic regression step, the enter method was used for all variables with a p-value <0.2 in the bivariate analysis. The statistical significance was set at the 5% level. Results: In the group prior to the DTG, there was a predominance of males (67.5%), non-white color / race (60.3%), to have born in the state of Espírito Santo (74.2%) and a marital status in the category of unmarried (85.2%). Regarding education, 59.3% had a high level of education. The mean age presented by this group was 44.2 ± 11.8 years (mean ± standard deviation) (95% CI: 42.5-45.9). Regarding the DTG group, there was also a predominance of males (69.8%), non-white color / race (77.4%), to have born in the state of Espírito Santo (73.6%) and an unmarried marital status (88.7%). Regarding education, 50.9% had a high level of education. The mean age of this group was 40.7 ± 14 (95% CI: 37.2-44.5). The study revealed that individuals treated with DTG were almost ten times more likely to have an undetectable final viral load have been treated before the introduction of DTG. Those undergoing treatment prior to DTG were less likely to have a discordant immune response. Conclusion: The present study identified a profile of male individuals, young adults, with a non-white declared race, of unmarried marital status, with a high level of education and born in Espírito Santo. There was a higher probability of undetectable final viral load and discordant immunological response among those treated with DTG